Improved biopsy accuracy in Barrett’s esophagus with a transparent cap - Chen, Bai-Li (World journal of gastroenterology : WJG, 2014)
AIM:To evaluate the efficacy of endoscopy with a transparent cap on biopsy positioning in Barrett’s esophagus(BE).METHODS:One hundred and sixty-eight patients with suspected BE at endoscopy were enrolled in our study from November 2007 to December 2009 and divided into two groups:transparent cap group(n=60)and control group(n=108).Endoscopy with or without a transparent cap and subsequent biopsy of suspected lesions were performed by five experienced endoscopists in our hospital.In both groups,two biopsy specimens were taken from each patient,and the columnar epithelium or goblet cells in histological assessment were used as the diagnostic standard for BE.RESULTS:In the transparent cap group,41 cases were tongue type,while 17 and two cases were identified as island type and circumferential type,respectively.In the control group,65 tongue-type cases were confirmed,with 38 island-type and five circumferential-type cases.Moreover,there was no significant difference with regard to the composition of endoscopic BE types in the two groups(P>0.05).In the biopsy specimens,BE was detected in 50 cases in the transparent cap group(83.3%,50/60),whereas the detection rate in the control group(69.4%,75/108)was lower compared to that in the transparent cap group(P<0.05).In addition,goblet cells were recognized in only eight cases(all with columnar epithelium)(8/60,13.3%)in the transparent cap group,with 11 cases in the control group.CONCLUSION:Transparent cap-fitted endoscopy can guide biopsy positioning in BE without other accompanying complications,thus increasing the detection rate of BE.